Genetic transformation and regeneration of mature tissues of woody fruit plants bypassing the juvenile stage - Cervera, Magdalena; Juárez, José; Navarro, Antonio; Pina, José A.; Durán-Vila, Núria; Navarro, Luis; Pena, Leandro (2017)
Regeneration and transformation systems from mature plant material of woody fruit species have to be achieved as a necessary requirement for the introduction of useful genes into specific cultivars and the rapid evaluation of resulting horticultural traits. We report here, for the first time, a procedure for genetic transformation and regeneration of mature tissues of woody plants that overcomes the long juvenile periods and high heterozygosity that are characteristic of most of these species. An improved regeneration frequency from mature explants was obtained by invigoration of the plant material through grafting of mature buds on juvenile seedlings. Co-cultivation of the explants in feederplates after inoculation with Agrobacterium tumefaciens resulted in enhanced transformation frequencies. Furthermore, in vitro shoot-tip grafting of the regenerated mature shoots on seedling rootstocks provided a rapid and efficient system for plant production. Citrus is the most extensively grown fruit crop worldwide and sweet orange (Citrus sinensis L. Osbeck) accounts for approximately 70% of the Citrus total production. Mature transgenic sweet orange plants have been obtained, which flowered and bore fruit in 14 months.